Statistical Analysis of Wind Speed for the Probability Evaluation of Cancelled Departure for Catamarans and Ferries (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
Weather data bases are important in optimizing a range of economic activities, such as maritime traffic. In this paper, a statistical analysis of data has been carried out, which includes the interpretation of the results with an emphasis on the analysis of consequences for local population. The proposed procedure is supported by realistic data for wind speed and direction measured at meteorological station Split in the period from 2002 to 2011. Using available data, the annual as well as seasonal wind roses for the specified location are shown. Furthermore, wind speed data are approximated by the Weibull's probability distribution that enables estimating the probability of exceeding a particular wind speed, i.e. Beaufort number for this location. Thus, the probability of cancelled departure for catamarans, as well as ferries from the Split city port is determined for the annual level as well as for each season. The obtained results provide a more detailed insight into the important occurrence of cancelled departure of catamarans and ferries, significant for the lives of the islanders gravitating to Split.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.